Study of genetic diversity of wild orange-spotted grouper (Epinephelus coioides) in Terengganu, Malaysia - Shaidatul Nadia binti Waludin (Kulliyyah of Science, International Islamic University Malaysia, 2018)
Orange-spotted groupers (Epinephelus coioides) are marine fish which can be found in Malaysia and are economically important. For such a significant commercial fish, surprisingly little is known about the biology of the orange-spotted grouper, and there is a lack of accurate catch data, particularly as the species is often misidentified. Orange-spotted grouper populations are believed to be decreasing due to overfishing and fish farmers' dependency on its wild seed fish. Hence, the aim of this study was to investigate the genetic diversity and population structure of wild orange-spotted grouper in Terengganu via partial cytochrome b (cyt-b) gene analysis. DNA of 114 wild fish from Besut, Setiu, Kemaman and Dungun, Terengganu was extracted. Polymerase chain reaction (PCR) amplification was conducted using cyt-b primers, and a sequence of 460 bp in length was obtained for each samples. Phylogenetic analysis was performed to study the relationships among the individuals. The haplotype and nucleotide diversities of the populations were investigated to measure genetic diversity. The haplotype diversity (Hd) and nucleotide diversity (Pi) of E. coioides was relatively low for all populations in Terengganu. Moreover, 18 haplotypes were identified among the 114 individuals, with 83 individuals sharing a single haplotype (Hap01). Pairwise genetic distance analysis between haplotypes was from 0.023 to 0.000. In consistent to the low haplotype and nucleotide diversity, the Tajima's D showed a non-significant negative value in all Terengganu localities, suggesting the occurrence of population size expansion, after the events of genetic bottleneck that has the probability to cause an excess of low frequency of polymorphism. As for population structure, Fst pairwise analysis shows low genetic differentiation in different areas of Terengganu except, between Dungun and Kemaman. These findings concurred with those of a previous study that reported that overfishing and seed fish dependent can led to a decline in grouper numbers and in turn, a genetic deprivation in the population.